The Impact of Colonialism on the Development of Marketing in Nigeria: A Dyadic Analysis - Ebitu; Tom, Ezekiel (British Journal of Marketing Studies, 2016)
For about a century, the British colonial masters took full control of the political, economic and even the social life of the people called Nigerians today. This paper traces the impact of colonialism on the development of marketing in Nigeria. It takes a look at the pre-colonial marketing practices of the nation-states and kingdoms and the development or otherwise of marketing during the era of colonialism in Nigeria. It points out that what the colonialists did or failed to do to develop marketing theory and practice in Nigeria. It adopts a theoretical review of related literature and also took a position on this topic that while the colonialists had set-up some institutions, they did very little to strengthen the institutions and develop human capital in the country. The article makes far-reaching recommendations that will help enrich marketing theory and practice, strengthen marketing institutions and contribute to the general well-being of the people and the nation as a whole.